Hermeneutics and Phenomenology in Human and Social Sciences Research. (2020)
This article of reflection problematizes the relationships between phenomenology and hermeneutics as epistemic places of research work through a documentary approach built in two phases. First, the text reflects on the terminological use present in the paradigms, approaches, epistemological perspectives, and research methods, thereby identifying that there is no criteria univocity in its references and approaches about research methodology treaties. Likewise, it is evident that there are methodological proposals that include phenomenology and hermeneutics in a complementary, articulated, or isolated way without allowing precise places of understanding that allow to locate their application in research. Based on the aforementioned, the second phase proposes an individual approach to the background and comprehensions of phenomenology and hermeneutics, identifying particularities that characterize them, possible theoretical-practical differences and approaches that can be established in view of their relevance from the epistemic and methodological framework of research in human and social sciences.